2012
DOI: 10.1016/j.cmet.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Srf-Dependent Paracrine Signals Produced by Myofibers Control Satellite Cell-Mediated Skeletal Muscle Hypertrophy

Abstract: Adult skeletal muscles adapt their fiber size to workload. We show that serum response factor (Srf) is required for satellite cell-mediated hypertrophic muscle growth. Deletion of Srf from myofibers and not satellite cells blunts overload-induced hypertrophy, and impairs satellite cell proliferation and recruitment to pre-existing fibers. We reveal a gene network in which Srf within myofibers modulates interleukin-6 and cyclooxygenase-2/interleukin-4 expressions and therefore exerts a paracrine control of sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 31 publications
4
127
0
3
Order By: Relevance
“…20,21 However, miR-199a-5p expression levels are the highest in MT, which suggests that a transcriptional activator of miR-199a-5p expression might also increase during myogenic differentiation. In support of this hypothesis, SRF and its transcriptional cofactors MRTF (myocardin-related transcription factor)-A and MRTF-B, have been shown to increase in expression levels during myogenic [24][25][26] Based on evolutionary conservation, we generated several luciferase reporter constructs (2, 1, 0.8, 0.5, and 0.2 kb) using DNA sequences upstream of the miR-199a-2 locus that contained either the SRF CArG box (labeled S1 or S2 for Site 1 or Site 2, respectively) along with a conserved E-box site to which the myogenic helix-loop-helix factors could potentially bind (Figures 2a and b). Overexpression of SRF and MRTF factors, specifically MRTF-A, was sufficient to strongly induce endogenous miR-199a-5p transcript in human primary MB (Figure 2c).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…20,21 However, miR-199a-5p expression levels are the highest in MT, which suggests that a transcriptional activator of miR-199a-5p expression might also increase during myogenic differentiation. In support of this hypothesis, SRF and its transcriptional cofactors MRTF (myocardin-related transcription factor)-A and MRTF-B, have been shown to increase in expression levels during myogenic [24][25][26] Based on evolutionary conservation, we generated several luciferase reporter constructs (2, 1, 0.8, 0.5, and 0.2 kb) using DNA sequences upstream of the miR-199a-2 locus that contained either the SRF CArG box (labeled S1 or S2 for Site 1 or Site 2, respectively) along with a conserved E-box site to which the myogenic helix-loop-helix factors could potentially bind (Figures 2a and b). Overexpression of SRF and MRTF factors, specifically MRTF-A, was sufficient to strongly induce endogenous miR-199a-5p transcript in human primary MB (Figure 2c).…”
Section: Resultsmentioning
confidence: 89%
“…51,52 The induction of miR199a-5p expression levels, coinciding with increased SRF expression during myogenic differentiation, further supports the hypothesis that SRF is a regulator of muscle hypertrophic growth while suppressing MSC proliferation. 25 Recently, it has been shown that induction of WNT7a can induce muscle hypertrophy by activating the PI3K/AKT pathway in myofibers. 53 Given that we demonstrated miR-199a-5p overexpression promotes myoblast proliferation but has a modest effect in MT, one might hypothesize that miR199a-5p's regulation of WNT signaling may be acting in a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the reason behind these findings, we examined for relevant molecules and found that serum response factor (SRF)-a key transcription factor in SkM lineage commitment-was involved, with higher baseline expression in hDE-MSCs compared with adult BMMSCs. SRF is known to be a crucial transcription factor for muscle-specific gene expression, involved in the control of MyoD expression in skeletal myoblasts and in satellite cell activation during muscle regeneration [18,19]. Our results demonstrate that hDE-MSCs can be good candidates for SkM regeneration, and the role of SRF in contributing to the efficient SkM differentiation of hDE-MSCs.…”
mentioning
confidence: 55%
“…En effet, la seule restauration de la fusion des cellules satellites aux fibres en croissance est suffisante pour rétablir la croissance musculaire. Ainsi, Srf semble être un régulateur clé de l'hypertrophie physiologique du muscle squelettique : en réponse à un signal mécanique, Srf stimule, par un mécanisme paracrine, la prolifération des cellules satellites et leur fusion aux fibres musculaires en croissance (Figure 2) [9]. Il est intéressant de remarquer que lorsque nous induisons l'hypertrophie musculaire par l'activation de la voie Akt, donc en l'absence d'une augmentation du signal méca-nique, il n'y a pas de recrutement de cellules satellites et Srf n'intervient utilisé une approche globale permettant la mise en évidence de gènes dont l'expression est augmentée en réponse à une activation de Srf dans les myotubes.…”
Section: Plasticité Du Muscle Squelettiqueunclassified